The Complete Blood Count Sepsis Index Using Monocyte Distribution Width for Early Detection of Sepsis in Patients Without Obvious Signs - Scott Levin, PhD; Nima Sarani, MD; Jeremiah Hinson, MD, PhD; Melissa Naiman, PhD; Chad Cannon, MD; Aria Smith, MS; Benjamin Steinhart, MS; Arnaud DeBraine, BS; Sarah Kehoe, PhD; Bryan Immhoff, MD; Yasir Taribichi, MD; Alexandra Malinovska, MD; et al. (Critical Care Explorations)
OBJECTIVES:. Exploiting the complete blood count (CBC) with differential (CBC-diff) for early sepsis detection has practical value for emergency department (ED) care, especially for those without obvious presentations. The objective of this study was to develop the CBC Sepsis Index (CBC-SI) that incorporates monocyte distribution width (MDW) to enhance rapid sepsis screening. DESIGN:. A retrospective observational study. SETTING:. The ED of the University of Kansas Medical Center, United States. PATIENTS:. All adult patients (age 18 or over) presenting to the ED between August 8, 2020, and April 1, 2022, that received a CBC-diff as part of routine clinical care. INTERVENTIONS:. MDW, WBC count, and neutrophil-to-lymphocyte ratio were used to develop a CBC-SI (0 low to 5 high risk) for early sepsis detection. The diagnostic performance of CBC-SI was evaluated for patients with and without obvious early signs of sepsis. MEASUREMENTS AND MAIN RESULTS:. In a cohort of 51,407 ED visits, 1,683 (3.3%) met sepsis criteria; 1,343 (79.8%) septic patients presented with obvious signs and 340 (20.2%) without. The overall area under the curve of the CBC-SI was 0.83 (95% CI, 0.81–0.85). A CBC-SI of greater than or equal to 1 point exhibited a sensitivity of 83.1% (95% CI, 79.9–86.2%) and specificity of 64.8% (95% CI, 64.0–65.5%). Superior performance was observed in the patient subgroup presenting without obvious signs; greater than or equal to 1 point, 81.1% (95% CI, 73.2–88.9%) sensitivity and 69.1% (95% CI, 68.3–69.9%) specificity. Septic patients without obvious signs exhibited delays in antibiotic administration from arrival (median 4.7 vs. 3.4 hr; p < 0.001) and higher rates of ICU admission (43.8% vs. 27.9%; p < 0.001) and in-hospital mortality (14.7% vs. 9.8%; p = 0.011) compared with the septic subgroup presenting with obvious signs. CONCLUSIONS:. The CBC-SI demonstrated strong performance for early sepsis detection. Its performance was best for nonobvious presentations, suggesting highest utility in a subgroup that is most susceptible to delayed interventions and poorer outcomes.